Glacier retreat and perception of climate change by local tourism stakeholders: the case of Chamonix-Mont-Blanc in the French Alps - Christophe Clivaz; Alexandre Savioz (Via@)
Climate change strongly impacts tourism activity in the Alps. In this context, how are these changes perceived by tourism stakeholders at the local level? According to the anthropological approach to climate change, the latter is characterized by a multitude of phenomena that generally remain imperceptible to our senses, and this makes understanding matters of climate all the more complicated. By studying the case of the Chamonix valley, characterized by a prominent presence of glaciers in the landscape, we seek to determine the extent to which the climate issue is better understood when it materializes in tangible problems such as glacier retreat, which in the eyes of local residents constitutes a visible threat to the tourist potential of the region. Our analysis shows that this is not the case and that the significant presence of glacial landscapes does not facilitate appropriation of the climatic phenomenon by local tourism stakeholders.